+0  
 
0
164
1
avatar
Solve for x

2(27)^x = 9^(x-1)
Guest Mar 28, 2012
Sort: 

1+0 Answers

 #1
avatar+3071 
0
2*(27^x) = 9^(x-1)
ln on both sides:
ln( 2*(27^x) ) = ln( 9^(x-1) )
x * ln( 27 ) + ln( 2 ) = (x-1) * ln( 9 )
x * ln( 27 ) + ln( 2 ) = x * ln( 9 ) - ln( 9 )
x * ln( 27 ) = x * ln( 9 ) - ln( 9 )-ln( 2 )
x * ln( 27 ) = x * ln( 9 ) - ln( 9 )-ln( 2 )
x * ln( 27 ) -x * ln( 9 ) = - ln( 9 )-ln( 2 )
x * ( ln( 27 ) - ln( 9 ) ) = - ln( 9 )-ln( 2 )
x = (- ln( 9 )-ln( 2 )) / ( ln( 27 ) - ln( 9 ) )
[input](- ln( 9 )-ln( 2 )) / ( ln( 27 ) - ln( 9 ) )[/input]
admin  Mar 28, 2012

17 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details